The size-dependent morphology of Pd nanoclusters formed by gas condensation. Issue 46 (9th November 2015) - Pearmain, D.; Park, S. J.; Abdela, A.; Palmer, R. E.; Li, Z. Y.
Abstract : A scanning transmission electron microscopy (STEM) study of mass-selected Pd nanoclusters in the size range of 887 to 10 000 atoms, formed by inert gas aggregation, reveals a strong size-dependence of cluster morphology. Abstract : Size-selected Pd nanoclusters in the size range from 887 to 10 000 atoms were synthesized in a magnetron sputtering, inert gas condensation cluster beam source equipped with a time of flight mass filter. Their morphologies were investigated using scanning transmission electron microscopy (STEM) and shown to be strongly size-dependent. The larger clusters exhibited elongated structures, which we attribute to the aggregation, through multiple collisions, of smaller clusters during the gas phase condensation process. This was confirmed from the atomically resolved STEM images of the Pd nanoclusters, which showed smaller primary clusters with their own crystalline structures.